Perivascular Adipose Tissue (PVAT) in Health and Disease - Maik Gollasch (Frontiers Research Topics, 2018)
In 1991, Soltis and Cassis (Clin Exp Hypertens A 1991 13:277-296) published the first paper that the fat tissue around an artery - perivascular adipose tissue or PVAT - changed how the artery contracted to norepinephrine. Followed later by important work showing that PVAT itself contained vasoactive molecules, the scientific community recognized that PVAT was not simply a store of fat but is a vasoactive tissue that contributes to the functioning and status of the vessel it surrounds. Our goal for this Frontiers Research Topic is to highlight the significant reach of PVAT in vascular function, from contractility to growth in health and in disease. In doing so, we explicitly place findings that can be taken advantage of in creating new therapies for cardiovascular diseases that continue to challenge our community. These include hypertension, atherosclerosis, and diabetes to name a few.